(untitled) (Research, Society and Development, 2020)
Lipomas are defined as benign neoplasms that have mesenchymal origin, they present slow growth and are quite unusual to find in the oral cavity, although it is often found in other regions of the body, especially in the extremities and in places where there is a greater presence of adipocytes , given that this tumor histologically consists of mature adipocytes. Clinically, it is characterized as nodular lesions that can be sessile or pedicular and is diagnosed, usually between the fourth and sixth decades of life. The present study will interrelate the report of a rare clinical case of large lipoma in the submandibular region in a male patient with the literature from a narrative / critical review through access to the main databases, namely; PubMed (Medline), Web Of Science, Scopus and Lilacs using DeCS controlled vocabulary terms.